Salivary Hormones and Quality of Life in Female Postmenopausal Burning Mouth Patients-A Pilot Case-Control Study - Božana Lončar-Brzak; Valentina Vidranski; Ana Andabak-Rogulj; Danica Vidović-Juras; Ivana Todorić-Laidlaw; Dragana Gabrić; Ivana Škrinjar (MDPI AG, 2020)
The objective of our study was to investigate salivary levels of estradiol, progesterone and dehydroepiandrosterone (DHEA), and quality of life, in female postmenopausal women with burning mouth syndrome. The study included new patients diagnosed with burning mouth syndrome and excluded local and systemic causes. Unstimulated saliva samples were taken in the morning from 9 AM and 11 AM and immediately frozen for hormone analysis. The patients filled out a self-perceived quality of life questionnaire Oral Health Impact Profile-14 and determined the intensity of mucosal symptoms according to the visual-analog scale grading 0 to 10. A total of 40 patients were included. The study group had significantly lower levels of salivary estradiol. No difference was observed in levels of progesterone and DHEA between the groups. The levels of salivary hormones did not exhibit a significant correlation according to the Spearman correlation test with a self-perceived quality of life questionnaire (OHIP-14) in the study group or in the control group. Further research on a larger number of patients is needed to verify these results. This information might help to enable more precise and efficient treatment.